REFLECTANCE AND TRANSMITTANCE OF TE AND TM POLARIZATION PLANE WAVE BY AN ARRAY OF DIELECTRIC CYLINDERS - Ginting, Oeken
In this final project, we formulate a general solution for the electromagnetic scattering using an array of a cylindrical dielectric system. We start by deriving and solving the Maxwell equation in cylindrical geometry to obtain the simplified scattering coefficients. The coefficients will be used to find the reflectance and transmittance equation. The formulation is then implemented numerically using MATLAB to plot the reflectance and transmittance graph against the incoming wave wavelength. We succeeded to reproduce referenced results with our formulated theory and program.